Water management, Middle East peace and a role for the World bank - Catherine Brown; Hossein Askari (PSL Quarterly Review, 2001)
The region comprising North Africa and the Middle East is the driest in the world. Thus conflicts over water have been a part of the landscape. These conflicts overwater are invariably seen as a zero sum game; such a view does not incorporate the notion that water is an economic good and is therefore scarce. Given the limitation of competitive markets, optimal water allocation could only but help. However, even if one country allocates water efficiently within its own territory, its allocation could be sub-optimal if water interdependencies with other countries are not incorporated in a regional optimization model. The World Bank is in the best position to adopt a regional optimization model and thus ameliorate water conditions in the Middle Eastand in other regions around the world.